‘It was just the given thing to do’: exploring enablers for high childhood vaccination uptake in East London’s Bangladeshi community—a qualitative study - Sadie Bell; Sandra Mounier-Jack; Ifra Ali (BMJ Public Health)
Background Despite being an underserved ethnic minority group, characteristics which have been associated with low vaccine uptake, the Bangladeshi community in the UK exhibits high childhood vaccination uptake for several vaccines, including measles, mumps and rubella compared with several ethnic groups. This study explored key enablers for early childhood vaccination uptake among the Bangladeshi community in East London, UK.Methods A qualitative study using semi-structured interviews was conducted with 23 Bangladeshi parents 11 primary healthcare professionals (HCPs) and 5 community service providers (CSPs) involved in delivering childhood vaccination services, predominantly in the East London borough of Tower Hamlets. Parents were recruited purposively from the community while HCPs and CSPs were recruited from relevant organisations. The Social Ecological Model (SEM) was used as a theoretical framework for data collection and analysis. Data were analysed thematically.Results Multilevel vaccination enablers identified by parents, HCPs and CSPs across the different levels of the SEM included: parental trust in the immunisation programme and HCPs; a rigorous call and recall service; the normalisation of receiving childhood vaccinations within the Bangladeshi community and the availability of culturally tailored and accessible vaccination services.Conclusions This study highlights how multi-level trust in a vaccination programme can propel positive vaccine uptake in an underserved, ethnic minority population. Our findings suggest culturally sensitive, person-centred delivery of vaccination services, alongside leveraging community dynamics and trusted social networks, are imperative to meeting the informational, linguistic and cultural needs that facilitate vaccine uptake within the Bangaldeshi community. We recommend using existing trusted community networks to disseminate tailored vaccine information and actively reminding parents about due vaccinations to promote uptake amongst other underserved, ethnic minority communities with low uptake in high-income settings. Further research involving non-immunising parents is recommended to gain more comprehensive insight into vaccine decision-making within this community.